Pemindahan Ibu Kota Negara Perspektif Civil society - Aziz SR, Abdul (Journal of Politics and Policy, 2023)
A country moving its capital is a natural and normal thing to do if the reasons are objective. Many countries do that. Indonesia is also in the process of doing so. President Joko Widodo plans that on August 17 2024 the proclamation of independence ceremony can be held at the new IKN. Various criticisms from many groups, especially civil society, have emerged regarding President Joko Widodo's IKN project. Starting with a feasibility study that was not transparent and anti-discussion, followed by an academic paper that was bad quality. The IKN project is considered to be fraught with the business interests of political elites and capital owners. Apart from that, the IKN project is seen as having the potential to damage the environment and be fraught with agrarian conflict. The costs required for IKN in East Kalimantan are truly enormous and will definitely drain the APBN. IKN is not a priority at this time. IKN is also seen as an ambitious project that only serves to cover up President Joko Widodo's failures in all areas of life during his two terms of leadership.